2008
DOI: 10.1007/s00192-008-0731-7
|View full text |Cite
|
Sign up to set email alerts
|

Do preoperative cytokine levels offer a prognostic factor for polypropylene mesh erosion after suburethral sling surgery for stress urinary incontinence?

Abstract: When polypropylene meshes are used in reconstructive urogynecological surgery, the erosion rates vary from 3.3% to 14% and causative factors for such erosions are still unknown in many cases. Therefore, the aim of our study was to establish the role of immunologic factors in the process of polypropylene tapes erosions after suburethral sling procedures. Serum concentrations of tumor necrosis factor alpha, interleukin (IL)-2, IL-4, IL-5, IL-10, and interferon (IFN)-gamma were estimated in 123 patients suffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Polypropylene mesh implants are commonly used in human reconstructive surgery and result in implant-related erosions in 1% to 2% of cases. [4][5][6][7][8][9] Polypropylene implants induce a mild but persistent foreign body reaction in recipient tissues in multiple species, 9 so it is logical to assume that similar chronic foreign body reactions occur in dogs that receive polypropylene implants. Histologically, the mass removed from the tracheal lumen in the study reported here had features consistent with chronic inflammation and the tissue reaction induced by a foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Polypropylene mesh implants are commonly used in human reconstructive surgery and result in implant-related erosions in 1% to 2% of cases. [4][5][6][7][8][9] Polypropylene implants induce a mild but persistent foreign body reaction in recipient tissues in multiple species, 9 so it is logical to assume that similar chronic foreign body reactions occur in dogs that receive polypropylene implants. Histologically, the mass removed from the tracheal lumen in the study reported here had features consistent with chronic inflammation and the tissue reaction induced by a foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rechberger et al investigated the role between preoperative cytokine levels and PP mesh erosion after suburethral sling placement [24]. Preoperative serum IFN concentrations in a group of patients without mesh erosion were compared with preoperative levels for patients with mesh erosion.…”
Section: Host Response At a Cellular Levelmentioning
confidence: 99%
“…Rechberger et al observed that the serum levels of cytokines are higher in patients with erosion slings than in those with proper healing ( 5 ). Similarly, Di Vita et al demonstrated that the use of polypropylene for hernia repair is associated with high levels of interleukin-6 and interferon, when compared to traditional correction ( 6 ).…”
Section: Introductionmentioning
confidence: 99%